1995
DOI: 10.1002/1097-4679(199509)51:5<685::aid-jclp2270510514>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-theta brainwave neurofeedback training: An effective treatment for male and female alcoholics with depressive symptoms

Abstract: This was an experimental study of 14 alcoholic outpatients using the Peniston and Kulkosky (1989, 1991) brainwave treatment protocol for alcohol abuse. After temperature biofeedback pretraining, experimental subjects completed 20 40‐minute sessions of alpha‐theta brainwave neurofeedback training (BWNT). Experimentally treated alcoholics with depressive syndrome showed sharp reductions in self‐assessed depression (Beck's Depression Inventory). On the Millon Clinical Multiaxial Inventory‐I, the experimental subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 17 publications
6
93
0
3
Order By: Relevance
“…Following the session, with the participant in a relaxed and suggestible state, a therapy session is conducted between the participant and therapist where the contents of the imagery experienced is explored and ''abreactive'' experiences are explored (Peniston & Kulkosky, 1989, 1991. Saxby and Peniston (1995) reported on 14 chronically alcohol dependent and depressed outpatients using this same protocol of alpha-theta brainwave biofeedback. Following treatment, participants showed substantial decreases in depression and psychopathology as measured by standard instruments.…”
Section: Studies Of Eeg Biofeedback In Substance Abuse Treatmentmentioning
confidence: 98%
See 2 more Smart Citations
“…Following the session, with the participant in a relaxed and suggestible state, a therapy session is conducted between the participant and therapist where the contents of the imagery experienced is explored and ''abreactive'' experiences are explored (Peniston & Kulkosky, 1989, 1991. Saxby and Peniston (1995) reported on 14 chronically alcohol dependent and depressed outpatients using this same protocol of alpha-theta brainwave biofeedback. Following treatment, participants showed substantial decreases in depression and psychopathology as measured by standard instruments.…”
Section: Studies Of Eeg Biofeedback In Substance Abuse Treatmentmentioning
confidence: 98%
“…This classification is based on the original randomized and controlled study of the Peniston Protocol (Peniston & Kulkosky, 1989, 1991 and multiple observational and uncontrolled studies that preceded and followed these studies (Bodenhamer-Davis & Calloway, 2004;Burkett et al, 2003;DeBeus et al, 2002;Fahrion, 1995;Fahrion et al, 1992;Finkelberg et al, 1996;Saxby & Peniston, 1995;Skok et al, 1997). Using these criteria and based on reported studies to date the Scott-Kaiser modification of the Peniston Protocol can also be classified as probably efficacious (Level 3) when combined with residential rehabilitation modalities in stimulant abusers.…”
Section: Criteria Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since excessive expectations (i.e., that alpha feedback could allow persons to reach sublime states of consciousness) turned out to be unrealistic, interest in the phenomenon died away during the 1980s. However, during the past decade alpha feedback underwent a renaissance, which was initiated by replicated reports that alcohol withdrawal is substantially supported by combined alpha-theta feedback training (e.g., Peniston & Kulkosky, 1989;Saxby & Peniston, 1995;Kelley, 1997).…”
mentioning
confidence: 99%
“…It has already been used as a therapeutic method in various mental illnesses, such as depression (Putman, 2002), attention-deficit/hyperactivity (Fuchs et al, 2003;Rossiter, 2004;Strehl et al, 2006;Kropotov et al, 2007), obsessive compulsive disorder (Hammond, 2003), epilepsy (Kotchoubey et al, 2001), anxiety and affective disorders (Hammond, 2005). Moreover, some studies have confirmed its efficiency in weakening the neuropsychological traits of substance and alcohol dependence (Saxby and Peniston, 1995;Masterpasqua and Healey, 2003;Scott et al, 2005;Sokhadze et al, 2008). Gruzelier provides important aspects and recommendations to this direction by examining spheres of cognitive, affective and behavioralenhancement with neurofeedback (Gruzelier, 2014a) as well as a range of fascinating insights about underpinnings from multimodal methodologies in addition to numerous methodological and theoretical issues (Gruzelier, 2014b;Gruzelier, 2014c;Gruzelier et al, 2014).…”
Section: Future Outlookmentioning
confidence: 99%